A prudência em Aristóteles como critério moral de justiça - Santos, André Marsiglia de Oliveira (2022)
Aristotelian prudence can be understood as an institute that applied a moral purpose to concrete cases of practical life. Morality, shared by an education that taught through laws, habit, and experience, aimed at the common good and the happiness of citizens in Greek cities. The current dissertation analyzes the relations between the Aristotelian moral prudence and the search for the justice of ancient times and aims to illuminate some paths of the search for the just in modern times